2006
DOI: 10.1001/archneur.63.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic Substrate of Mild Cognitive Impairment

Abstract: To define the neuropathologic findings in amnestic mild cognitive impairment (MCI) and early Alzheimer disease (EAD). Methods: The mean numbers of diffuse plaques, neuritic plaques (NPs), and neurofibrillary tangles (NFTs) in 4 neocortical regions and 4 ventromedial temporal lobe regions were counted in 10 patients with amnestic MCI and compared with the mean numbers in 23 normal control subjects and 10 patients with EAD, and then were compared with memory performance. All of the controls and patients were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
286
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(310 citation statements)
references
References 41 publications
21
286
0
1
Order By: Relevance
“…There is some, but still very limited, evidence that neuron loss may be more pronounced and neurofibrillary tangles may be more frequent in amygdala than in hippocampus in early stages of AD [2,20,33,34,43,47,52]. This may indicate more rapid progression or earlier onset of pathological changes in amygdala than hippocampus so that amygdala atrophy may have reached its maximum even before the conversion from MCI to AD.…”
Section: Discussionmentioning
confidence: 99%
“…There is some, but still very limited, evidence that neuron loss may be more pronounced and neurofibrillary tangles may be more frequent in amygdala than in hippocampus in early stages of AD [2,20,33,34,43,47,52]. This may indicate more rapid progression or earlier onset of pathological changes in amygdala than hippocampus so that amygdala atrophy may have reached its maximum even before the conversion from MCI to AD.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, the beginning of AD is generally preceded by an temporary phase known as MCI, when there is no significant increase in the senile Advanced Pharmaceutical Bulletin, 2016, 6(4), 531-539 plaques and neurofibrillary tangles. 14,41 These subjects exhibit a significant oxidative imbalance. 8,9,14 The findings of present study indicated that using captopril and valsartan during AD has attenuated the free radicals production of ROS and RNS, (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…In persons with mild cognitive impairment proximate to death, levels of Alzheimer's disease pathology Petersen et al, 2006) and cerebral infarction have been shown to be intermediate between levels in persons with no cognitive impairment and those with dementia. Neurofibrillary pathology in particular has been proposed as the pathologic substrate of mild cognitive impairment (Guillozet, Weintraub, Mash, & Mesulam, 2003;Riley, Snowden, & Markesbery, 2002) and, from a neuropathologic standpoint, mild cognitive impairment has been characterized as early Alzheimer's disease (Markesbery et al, 2006). Neither is the impact of age-related neuropathology confined to persons with mild cognitive impairment.…”
Section: Age-related Neuropathologymentioning
confidence: 99%